Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
10 - { [ ( x : 3 + 17 ) : 10 + 3 : 24 ] : 10 } = 5
[ ( x : 3 + 17 ) : 10 + 3 : 24 ] : 10 = 10 - 5 = 5
( x : 3 + 17 ) : 10 + 3 : 24 = 5 x 10
( x : 3 + 17 ) : 10 + 48 = 50
( x : 3 + 17 ) : 10 = 50 - 48
( x : 3 + 17 ) : 10 = 2
x : 3 + 17 = 2 x 10
x : 3 + 17 = 20
x : 3 = 20 - 17 = 3
x = 3 x 3 = 9
a) [(2x+14) : 4 - 3] : 2 = 1
(2x+14) : 4 - 3 = 1/2
(2x+14) : 4 = 1/2 + 3
(2x+14) : 4 = 7/2
2x+14 = 7/2 . 1/4
2x = 7/8 - 1/4
2x = 5/8
x= 5/8.1/2
x= 5/16
\(\left|x-2\right|+\left|2y-5\right|=0\)
\(\left\{{}\begin{matrix}\left|x-2\right|\ge0\forall x\\\left|2y-5\right|\ge0\forall y\end{matrix}\right.\)
\(\left|x-2\right|+\left|2y-5\right|\ge0\)
Dấu "=" xảy ra khi:
\(\left\{{}\begin{matrix}\left|x-2\right|=0\Rightarrow x=2\\\left|2y-5\right|=0\Rightarrow2y=5\Rightarrow y=\dfrac{5}{2}\end{matrix}\right.\)
\(\left|3y-2\right|+\left|xy-6\right|=0\)
\(\left\{{}\begin{matrix} \left|3y-2\right|\ge0\forall y\\\left|xy-6\right|\ge0\forall x;y\end{matrix}\right.\)
\(\Rightarrow\left|3y-2\right|+\left|xy-6\right|\ge0\)
Dấu "=" xảy ra khi:
\(\left\{{}\begin{matrix}\left|3y-2\right|=0\Rightarrow3y=2\Rightarrow y=\dfrac{3}{2}\\\left|xy-6\right|=0\Rightarrow\dfrac{3}{2}x=6\Rightarrow x=4\end{matrix}\right.\)
\(\left|x-\dfrac{1}{2}\right|+\left|2y-\dfrac{1}{3}\right|+\left|4z-5\right|\le0\)
\(\left\{{}\begin{matrix}\left|x-\dfrac{1}{2}\right|\ge0\forall x\\\left|2y-\dfrac{1}{3}\right|\ge0\forall y\\ \left|4z-5\right|\ge0\forall z\end{matrix}\right.\)
\(\Rightarrow\left|x-\dfrac{1}{2}\right|+\left|2y-\dfrac{1}{3}\right|+\left|4z-5\right|\ge0\)
\(\Rightarrow\left[{}\begin{matrix}\left|x-\dfrac{1}{2}\right|+\left|2y-\dfrac{1}{3}\right|+\left|4z-5\right|\ge0\\\left|x-\dfrac{1}{2}\right|+\left|2y-\dfrac{1}{3}\right|+\left|4z-5\right|\le0\end{matrix}\right.\)
\(\Rightarrow\left|x-\dfrac{1}{2}\right|+\left|2y-\dfrac{1}{3}\right|+\left|4z-5\right|=0\)
\(\Rightarrow\left\{{}\begin{matrix}\left|x-\dfrac{1}{2}\right|=0\Rightarrow x=\dfrac{1}{2}\\\left|2y-\dfrac{1}{3}\right|=0\Rightarrow2y=\dfrac{1}{3}\Rightarrow y=\dfrac{1}{6}\\\left|4z-5\right|=0\Rightarrow4z=5\Rightarrow z=\dfrac{5}{4}\end{matrix}\right.\)
\(x^3+x^2y-2x^2-xy-y^2+3y+x+2006\)
\(=x^2\left(x+y-2\right)-y\left(x+y-2\right)+y+x-2+2004\)
= 2004
Bài 2
\(a,\)\(\left(x^2+7\right)\left(x^2-49\right)< 0\)
Vì \(x^2+7>0\)\(\Rightarrow x^2-49< 0\)
\(\Rightarrow\left(x-7\right)\left(x+7\right)< 0\)
\(...\)
Bài 2:
a) \(\left(x^2+7\right).\left(x^2-49\right)< 0\)
\(\Leftrightarrow\hept{\begin{cases}x^2+7< 0\\x^2-49>0\end{cases}}\)hoặc \(\hept{\begin{cases}x^2+7>0\\x^2-49< 0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x^2< -7\\x^2>49\end{cases}\left(loai\right)}\)hoặc \(\hept{\begin{cases}x^2>-7\\x^2< 49\end{cases}}\)
\(\Leftrightarrow-7< x^2< 49\)
Mà \(x^2\ge0\)và \(x^2\)là 1 SCP
\(\Rightarrow x^2\in\left\{1;4;9;16;25;36\right\}\)
\(\Rightarrow x\in\left\{1;2;3;4;5;6\right\}\)
Vậy \(x\in\left\{1;2;3;4;5;6\right\}\)
b) (x-3).(2y+1)=7
(x-3).(2y+1)= 1.7 = (-1).(-7)
Cứ cho x - 3 = 1 => x= 4
2y + 1 = 7 => y = 3
Tiếp x - 3 = 7 => x = 10
2y + 1 = 1 => y = 0
x-3 = -1 ...=> x = 2
b: \(\Leftrightarrow\left(x-3;y+2\right)\in\left\{\left(1;11\right);\left(11;1\right);\left(-1;-11\right);\left(-11;-1\right)\right\}\)
hay \(\left(x,y\right)\in\left\{\left(4;9\right);\left(14;-1\right);\left(2;-13\right);\left(-8;-3\right)\right\}\)
c: \(\Leftrightarrow x\left(y-3\right)-y+3=3\)
=>(y-3)(x-1)=3
\(\Leftrightarrow\left(x-1;y-3\right)\in\left\{\left(1;3\right);\left(3;1\right);\left(-1;-3\right);\left(-3;-1\right)\right\}\)
hay \(\left(x,y\right)\in\left\{\left(2;6\right);\left(4;4\right);\left(0;0\right);\left(-2;2\right)\right\}\)